The Development Efforts of Motor Physical in Children Through Traditional Games and Creations of Used Items at TK Dharma Indria II Jember - Khutobah Khutobah (The Faculty of Teacher Training and Education The University of Jember Jember, Indonesia, 2019)
Nowadays, it is rare to see the children playing the traditional games, whereas the traditional games have many benefits in order to develop their motor physical. TK Dharma Indria II is one of the childhood institutions which facilitates various games supporting the children’s growth and development, however the games given are mostly adopted from abroad. Therefore, in order to balance the traditional and modern games, a game which is able to improve the motor physical and preserve the traditional culture as well as increase the number of existing traditional games was designed. The research method used the classroom action research which involved as many as 21 children of class B1. Based on the result analysis, the research was able to improve the motor physical in children from the cycle one, in which there were only 14 children who passed the learning, while in the cycle two increased into 19 children who passed the motor physical development, this research was able to develop the motor physical in children, in which 90% of the children’s motor physical achieved.